Imiona chrzestne nadawane w wybranych miejscowościach rzymskokatolickiej parafi i Pruchnik w okresie przedautomicznym - Romanik, Paweł; Kiper, Daniel (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The purpose of the following article is to examine the practice of giving baptismal names in the Catholic parish of the Latin rite in Pruchnik – situated in an area of the Polish- Russian border, which was part of the Habsburg monarchy after 1772. The research was narrowed down to the selected localities of the parish of Pruchnik – a small urban centre and surrounding villages in the period of 1776-1866. In the studied population, the catalogue of male names was more extensive than the female one. The vast majority of names were the Christian ones, especially biblical ones, the names of new Christian martyrs and saints of the Middle Ages. The most popular male names were: Jan, Antoni, Michał, Józef, Wojciech, Marcin, Jakub, Franciszek, Walenty, Andrzej. The female names most often given were as follows: Maria and Marianna, Katarzyna, Magdalena, Agnieszka, Anna, Franciszka, Zofi a, Antonina, Jadwiga, Salomea.